Synergistic Activation of the Nrf2-ARE Oxidative Stress Response Pathway by a Combination of Botanical Extracts - Missler, Stephen R.; Rajgopal, Arun; Roloff, Samantha J.; Scholten, Jeffrey D.; Burns, Charlie R.; Patterson, Jennifer A.; Pusateri, Donald J.; Gellenbeck, Kevin W.; Stern, Nate P.; Randolph, R. Keith; Lin, Yumei; Chuang, Jennifer; Kazlova, Valentina; Fast, David J. (Planta Medica International Open, 2016)
Many fruits and vegetables have been tested for their ability to scavenge free radicals. It is more likely, however, that the therapeutic effect of dietary fruits and vegetables on oxidative stress may be due to the induction of free radical defense mechanisms via activation of the Nrf2-ARE signaling pathway. In this study, we screened botanical extracts for the ability to activate the Nrf2 pathway using an antioxidant response element luciferase reporter cell line. Extracts of turmeric, padogda tree seed pod, and rosemary exhibited activity in the reporter assay, and a combination (1 : 3 : 5 w/w/w) stimulated a synergistic response greater than expected for an additive effect of the individual extracts. The results suggest a reduction in oxidative stress with botanical extracts selected for their ability to induce the Nrf2-ARE signaling pathway may be possible in healthy individuals who consume a synergistic blend of turmeric, pagoda tree seed pod, and rosemary extracts designed to upregulate the Nrf2-ARE signaling pathway.
Keywords: Curcuma longa; Zingiberaceae; Rosmarinus officinalis; Lamiaceae; Styphnolobium japonicum; Fabaceae; antioxidant response element; Nrf2